2009
DOI: 10.1002/cjce.20152
|View full text |Cite
|
Sign up to set email alerts
|

Mass transfer during air humidification in spouted beds

Abstract: This article presents the results obtained from analysing the impacts of bed media, static bed height, and the water-to-air mass flow ratios on the mass transfer coefficient and Colburn factor. The experimental data were compared with the correlations for mass transfer and the analogy between heat and mass transfer in conical spouted beds described earlier in literature. Moreover, the aim of the article is to present some new correlations of dimensionless groups for description of mass transfer and analogy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Spouted beds are typically used for drying, so that studies of heat transfer reported in the literature are mainly centered on that process [22][23][24][25][26]. Several authors have developed mechanistic models for heat transfer in spouted bed drying, requiring sophisticated numerical and mathematical methods for solving systems of differential equations [4,21,[27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Spouted beds are typically used for drying, so that studies of heat transfer reported in the literature are mainly centered on that process [22][23][24][25][26]. Several authors have developed mechanistic models for heat transfer in spouted bed drying, requiring sophisticated numerical and mathematical methods for solving systems of differential equations [4,21,[27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Although spouted bed technology has already been implemented in many applications, being the subject of numerous studies involving hydrodynamics and gas and solid flow patterns, heat transfer is a point that has been scarcely approached in the literature. Thus, certain authors have studied the influence of temperature on hydrodynamics, but heat transfer itself has hardly been addressed, with drying being the main subject approached by most papers related to heat transfer. In fact, drying has so far been the main and more popular application of spouted beds. Nevertheless, conical spouted beds have also performed well in the pyrolysis of biomass, plastics, and tires .…”
Section: Introductionmentioning
confidence: 99%
“…Due to this unique hydrodynamic behavior,spouted beds have been used in many applications such as pyrolysis (Arabiourrutia et al, 2007;Makibar et al, 2012), combustion (Rasul,2001), gasification (Bernocco et al, 2013), coating (Martins et al, 2008) and drying (Benelli et al, 2013). The main advantage of the spouted bed is a cyclic pattern of solids movement which enhances the heat and mass transfer between gas and solids as well as the long solids residence time (Makibar et al 2011,Kmiec et al 2009.However, there areimportant limitationssuch aslow annulus aeration which may cause dead zones and particle agglomeration, high pressure drop prior to onset of spouting, and slow solids turnover (Rovero et al, 2012).One of many modifications to the spouted bed is spouted fluidized bed (Zhong et al, 2006(Zhong et al, , 2008 which is achieved by introducing additional gas flow into annular region of a spouted bed. The spouted fluidized bed reduces the particle agglomeration, improves the gassolid contact, and enhances mixing.…”
Section: Introductionmentioning
confidence: 99%